Validating Program Fidelity: Lessons from the Delaware County Second Chance Initiatives - Miller, J. Mitchell (American journal of criminal justice, 2016)
Reentry programming for offenders has increased considerably since the passage of the Second Chance Act in 2008. This study presents findings from the implementation and process phases of a multi-stage program evaluation of two Second Chance Act funded initiatives in Delaware County, Ohio. Two distinct programs, one for offenders diagnosed with co-occurring mental health and substance abuse disorders and another for substance dependent offenders with minor children, were examined using a mixed-methodological research design incorporating process and outcome phases. Process findings focus on determinations of program fidelity and adherence to evidence-based practices. Discussion centers on the role of process evaluation in assessments of intervention effectiveness and the importance of establishing program fidelity prior to outcome analysis.